Isi pesan persuasif dalam advertorial media massa cetak - Martutik, Martutik (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
In general, the goal of this research is to explain persuasive messages in advertorial forms found in printed advertisements. The study employs a qualitative approach oriented toward discourse analysis theory. The research findings indicate that messages of product superiority, promises of fulfillment, factual status, and opinion status are used to establish a positive image of products. The content of persuasive messages in advertorial advertisements is engineered by capitalists to build the hegemony of potential customers and encourage consumptive actions.